Magnetofluidic spreading in microchannels - Zhu, Gui-Ping (2013)
We investigate the spreading phenomena caused by the interaction between a uniform magnetic field and a magnetic fluid in microchannels. The flow system consists of two liquids: a ferrofluid and a mineral oil. The ferrofluid consists of superparamagnetic nanoparticles suspended in an oil-based carrier. Under a uniform magnetic field, the superparamagnetic particles are polarized and represent magnetic dipoles. The magnetization of the magnetic nanoparticles leads to a force resulting in the change of diffusion behavior inside the microchannel. Mixing due to secondary flow close to the interface also contributes to the spreading of the ferrofluid. The magnetic force acting on the liquid/liquid interface is caused by the mismatch of magnetization between the nanoparticles and surrounding liquid in a multiphase flow system. This paper examines the roles of magnetic force in the observed spreading phenomena. The effect of particles on the flow field is also considered. These phenomena would allow simple wireless control of a microfluidic system without changing the flow rates. These phenomena can potentially be used for focusing and sorting in cytometry.